Preparation of a Key Tetraene Precursor for the Synthesis of Long Acenes. Issue 11 (26th February 2020) - Levet, Gaspard; Hung, Nguyen Khanh; Šámal, Michal; Rybáček, Jiří; Cisařová, Ivana; Jancarik, Andrej; Gourdon, André
Abstract : The tetraene 7, 7‐dimethoxy‐2, 3, 5, 6‐tetramethylenebicyclo[2.2.1]heptane is a key compound for the preparation of a large variety of acenes protected by a carbonyl bridge. We report herein a medium scale preparation in seven steps of this valuable starting material. Diels–Alder addition between 6, 6‐dimethtyl fulvene and maleic anhydride, followed by carboxylation, ozonolysis of the double bond, reduction of the four ester groups, then chlorination of the alcohol groups and dehydrochlorination give the target compound in 17 % overall yield. Abstract : The tetraene 7, 7‐dimethoxy‐2, 3, 5, 6‐tetramethylenebicyclo[2.2.1]heptane is a key compound for the preparation of a large variety of acenes, which are protected by a carbonyl bridge. Herein, a medium scale preparation in seven steps of this valuable starting material is reported.